Meta‐Analysis of Wheat QTL Regions Associated with Adaptation to Drought and Heat Stress. Issue 2 (1st March 2015) - Acuña‐Galindo, M. Andrea; Mason, R. Esten; Subramanian, Nithya K.; Hays, Dirk B.
ABSTRACT: Drought and heat are the two most important environmental constraints to wheat ( Triticum aestivum L.) production globally and are predicted to become more severe with global climate change. A number of recent studies have reported quantitative trait loci (QTL) for yield and agronomic traits in drought and heat‐stressed environments and for physiological traits that contribute to improved performance under stress. The objective of this study was to perform a meta‐analysis of reported QTL to identify meta‐QTL (MQTL) associated with adaptation to drought and heat stress. In the studies analyzed, QTL were reported for 81 different traits across a range of environments including both field and controlled experiments. A total of 854 individual QTL were reported, with 502 associated with drought stress, 234 with heat stress, and 118 with physiological traits in nonstressed environments. Individual QTL clustered into 66 MQTL regions distributed throughout the genome. There were 43 MQTL that co‐localized for both drought and heat stress, 20 specific for drought stress, 2 specific for heat stress, and 1 MQTL specific for physiological traits in nonstressed environments. Quantitative trait loci for plant height, days to maturity, kernel weight, spike density, and canopy temperature were most significantly associated with QTL for yield. Integration of 137 single nucleotide polymorphism (SNP) markers for heat‐ and drought‐responsive candidate genes identified 50 SNPs within MQTL confidence intervals, including genes involved in sugar metabolism, scavenging of reactive oxygen species, and abscisic‐acid‐induced stomatal closure. Identified MQTL and candidate genes can be targeted for future studies and genetic improvement of abiotic stress tolerance in wheat.